2018
DOI: 10.1177/1934578x1801301038
|View full text |Cite
|
Sign up to set email alerts
|

Lavandula Essential Oils: A Current Review of Applications in Medicinal, Food, and Cosmetic Industries of Lavender

Abstract: The global essential oil market has been steadily increasing in size over the past few years, and is estimated to reach ca. $7.5 billion USD per annum by 2018. Lavenders (Lavandula; Lamiaceae) contribute significantly to this market, yielding ca. 1500 tons of essential oils which are primarily used in cosmetics, personal care products, and medicines. Recent literature indicates that these oils may also have applications in food preservation and pest control, among others. The medicinal and pharmaceutical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
94
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 210 publications
(271 reference statements)
0
94
0
4
Order By: Relevance
“…From the comparison with literature data (see Table 5), a high level of quali-quantitative variability in the EO compositions emerged, probably due to the different areas of origin of the samples, the heterogeneity of the employed plant material and the different extraction methods. [18] In most studies, the dominance of the oxygenated monoterpenes was confirmed, [10,16,17,22] but both the total number of compounds and the major compounds varied. According to this, different chemotypes were recognized in L. dentata, i. e., i) 1,8-cineole/β-pinene (like the one in this study) in samples from Algeria [23,24] and Mexico; [25] ii) linalool/linalyl acetate in specimens from Palestine [14] and one accession from Tunisia; [13] iii) 1,8cineole/camphor/fenchone in almost all published EO compositions for Brazilian specimens [12,26,27] and Tunisia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…From the comparison with literature data (see Table 5), a high level of quali-quantitative variability in the EO compositions emerged, probably due to the different areas of origin of the samples, the heterogeneity of the employed plant material and the different extraction methods. [18] In most studies, the dominance of the oxygenated monoterpenes was confirmed, [10,16,17,22] but both the total number of compounds and the major compounds varied. According to this, different chemotypes were recognized in L. dentata, i. e., i) 1,8-cineole/β-pinene (like the one in this study) in samples from Algeria [23,24] and Mexico; [25] ii) linalool/linalyl acetate in specimens from Palestine [14] and one accession from Tunisia; [13] iii) 1,8cineole/camphor/fenchone in almost all published EO compositions for Brazilian specimens [12,26,27] and Tunisia.…”
Section: Discussionmentioning
confidence: 96%
“…Concerning the ecological role, different authors reported the antifungal and anti-ochratoxigenic activity of the EO of L. dentata against Aspergillus carbornarius, its deterrence ability towards Aedes albopictus oviposition, along with larvicidal, insecticidal, fumigant and antimicrobic activities. [3,11,[16][17][18] Regarding the EO biological activity, antioxidant properties, cytotoxic effects towards tumor cell lines, as well as neuroprotective, sedative, antidepressant and carminative abilities were documented. [3,14,17,19,20] In this framework, the work presented hereafter proposes a multidisciplinary study on L. dentata grown in Italy, combining a morphological and phytochemical study approach in order to: 1) describe the trichome morphotypes on leaves and flowers by means of Light Microscopy and Scanning Electron Microscopy; 2) evaluate the histochemical features to localize in situ the main compound classes of metabolites present in their secretions; 3) characterize the leaf and flower VOC emission profiles and analyze the composition of the EO obtained from the aerial parts at blooming.…”
Section: Introductionmentioning
confidence: 99%
“…is an important oil-bearing plant belonging to the mint family (Lamiaceae), which is cultivated as medicinal and garden plant, and for essential oil production worldwide [1]. Large and increasing volumes of lavender essential oil are applied in a wide range of home and personal care products, perfumery, aroma-therapy and alternative medicine [2]. During the last decade Bulgaria has emerged as the world's largest producer and exporter of lavender essential oil [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Large and increasing volumes of lavender essential oil are applied in a wide range of home and personal care products, perfumery, aroma-therapy and alternative medicine [2]. During the last decade Bulgaria has emerged as the world's largest producer and exporter of lavender essential oil [2,3]. This was related to expansion of the lavender growing areas, including establishment of new lavender fields in the country regions with diverse soil and climatic conditions, which have been traditionally used for growing other crops.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan başka bir çalışmada, organik domateslerden izole edilen V. dahliae mikroorganizmalarına karşı etkili bir biyofungisit olduğu ortaya koyulmuştur [11]. Diğer bir çalışmada ise karabaş otu yağı, bazı bakterilere karşı antibakteriyel etki göstermiştir [12][13][14]. Literatürdeki diğer çalışmalar ışığında karabaş otu yağının geniş kullanım alanına sahip önemli bir esansiyel yağ olduğu sonucuna ulaşılmıştır.…”
Section: Introductionunclassified